Pengaruh Kualitas Pelayanan Presepsi Harga dan Promosi Terhadap Kepuasan Pelanggan di DAN+DAN - Widiana, Windi; Surono, Surono (Journal of Economics, Bussiness and Management Issues, 2025)
This study aims to examine the influence of service quality, price perception, and promotional strategies on customer satisfaction, with customer satisfaction acting as a mediating variable in driving customer loyalty. The study population consists of Dan+Dan retail consumers who made purchases in early 2025. Using a purposive sampling method, data were gathered from 100 respondents through structured questionnaires. Data analysis was carried out using multiple linear regression with SPSS version 22. The findings reveal that service quality, price perception, and promotion significantly influence customer satisfaction. Furthermore, customer satisfaction serves as a key mediating factor that strengthens the relationship between those variables and customer loyalty. Among the predictors tested, service quality emerged as the most dominant factor, both directly and indirectly, in shaping customer loyalty. These results underscore the critical role of integrated service strategies, competitive pricing, and effective promotion in fostering customer satisfaction and long-term loyalty. Practically, this study suggests that retail businesses should focus on service excellence, value-based pricing, and engaging promotional efforts to enhance customer retention and brand competitiveness.